Progress in MXene‐based catalysts for oxygen evolution reaction - Jieli Chen; Xiaohong Gao; Jing Li; Zhenye Kang; Juan Bai; Tianjiao Wang; Yuliang Yuan; Chenghang You; Yu Chen; Bao Yu Xia; Xinlong Tian (Electron)
Abstract Electrochemical water splitting for hydrogen generation is considered one of the most promising strategies for reducing the use of fossil fuels and storing renewable electricity in hydrogen fuel. However, the anodic oxygen evolution process remains a bottleneck due to the remarkably high overpotential of about 300 mV to achieve a current density of 10 mA cm−2. The key to solving this dilemma is the development of highly efficient catalysts with minimized overpotential, long‐term stability, and low cost. As a new 2D material, MXene has emerged as an intriguing material for future energy conversion technology due to its benefits, including superior conductivity, excellent hydrophilic properties, high surface area, versatile chemical composition, and ease of processing, which make it a potential constituent of the oxygen evolution catalyst layer. This review aims to summarize and discuss the recent development of oxygen evolution catalysts using MXene as a component, emphasizing the synthesis and synergistic effect of MXene‐based composite catalysts. Based on the discussions summarized in this review, we also provide future research directions regarding electronic interaction, stability, and structural evolution of MXene‐based oxygen evolution catalysts. We believe that a broader and deeper research in this area could accelerate the discovery of efficient catalysts for electrochemical oxygen evolution.